Swordfish Market Analysis Report Barbados - United Nations Conference on Trade; Development (United Nations, 2023)
This report documents the outcomes of the investigation of the market potential (both local and export) for swordfish (Xiphias gladius). The objective of this preliminary study is to expand sustainable production opportunities available within the Barbados quota allocations for swordfish under the International Commission for the Conservation of Atlantic Tunas (ICCAT). The report begins with an introduction of the UNCTAD-DOALOS “Evidence-based and policy coherent Oceans Economy and Trade Strategies